Consequences of Childhood Sexual Abuse on Mental Health during Adulthood - Bhattachary, Munia; Sharan, Anjali Midha; Kaul, Sakshi (International Journal of Psychosocial Rehabilitation, 2020)
Several experiments indicate that early interactions lead to personality formation and character growth. When a individual is harmed in this process, especially where the abuse is sexual in nature, his life becomes scarred for life. During adulthood it can cause multiple complications. This analysis addresses in specific the emotional problems confronting people who have a history of sexual exploitation of children. The report discusses 39 research on adolescent sexual assault and its effects conducted between 1986 and 2011 and provides an overview of disparities in mental health problems with relation to class. The study also addresses several other causes in relation to childhood sexual assault that may impact an individual’s mental wellbeing. Several findings are addressed in depth, including the Twin Findings and the Christchurch retrospective research. This study reflects on technologies and Big Data in the digital world and how the outcomes of the experiments have been changed.